Moldova : Water Security Diagnostic and Future Outlook - Smets, Susanna; Midgley, Amelia; Mao, Zhimin; Vladicescu, Veaceslav; Neumann, James E.; Strzepek, Ken; Pricop, Felicia (World Bank, Washington, DC, 2020)
Over the past two decades Moldova has achieved major development results: poverty more than halved between 2007 and 2014, and shared prosperity for the poorest households rose sharply. Yet Moldova’s growth model is volatile, unsustainable, and is losing strength. Water underpins much of Moldova’s ability to rekindle dynamism in its economy and to provide outcomes for the health and well-being of its people and environment. Yet gaps remain in understanding the country’s water resources endowments. This diagnostic suggests that in 2018 water availability is not a binding constraint to development. Even in the presence of future changes in demand, there are limited or manageable physical constraints to water security. Going beyond a focus on the water balance, this report assesses Moldova’s water security and identifies important water-related challenges that may hinder progress in economic and human development. Moldova’s water security is threatened by poor infrastructure and suboptimal institutional performance. Through an assessment of service delivery, water resources management and risk mitigation, and an analysis of institutional arrangements and sector expenditure data, this diagnostic establishes a set of policy recommendations on how water should be sustained and leveraged to support Moldova’s development. This report provides a new, comprehensive, and balanced view of water security in Moldova, highlighting the complex water issues that Moldova must tackle to improve its water security. It seeks to elevate water security as an issue critical for national development by providing stakeholders with a stocktaking and outlook on water-related risks, and opportunities in which water can contribute to economic growth and poverty reduction.